Developing curricular‐content and systems‐related impact indicators for intellectual disability awareness training for acute hospital settings: A modified International Delphi Survey. (5th December 2021) - Taggart, Laurence; Marriott, Anna; Cooper, Madeline; Atkinson, Dave; Griffiths, Lynn; Ward, Cathy; Mullhall, Peter
Abstract: Aim: To identify, and reach consensus on, curricular‐content and delivery methods, as well as ways to maximize the impact of intellectual disability awareness training programmes in acute hospital settings. Background: With the continuing evidence of avoidable deaths and unwarranted variations in the quality of care to people with an intellectual disability in acute hospitals, it could be purported that current training provided to hospital staff appears to be making a minimal difference in the care provided to this population. Design: A two‐round modified Delphi survey was conducted between June 2020–January 2021. Methods: International experts from primary healthcare and hospital settings, and intellectual disability health fields participated in the survey. Initial curricular‐content items were developed from the literature, and based on the combined clinical and academic experience base of the authors. Items were evaluated in terms of agreement/consensus, importance and stability of responses. There were 57 expert responses in Round 1 and 45 in Round 2. Results: The consensus was reached with regard to 55 of 65 curricular‐content indicators relating to Aims, Design, Content and Delivery. Ten curricular‐content indicators failed to be agreed on relating to the mode of training delivery. With regard to systems‐related impact indicators, 28 out of 31 reached consensus. The expert panel identified and agreed on seven system barriers that could obstruct the successful implementation of the awareness training programmes in acute hospital settings. Conclusions: This is the first international Delphi survey to agree on curricular‐content and identify systems‐related facilitators for intellectual disability awareness training. Potential system barriers have been highlighted which could be addressed by systemic improvement. Implications for developing, and robustly testing the efficacy of, intellectual disability awareness training programmes are discussed, as are the implications for other cognitively impaired populations. Impact: In order to maximize the impact, investment in acute hospital staff education will need to be accompanied by wider changes to systems and structures concerning the governance of service provision for people with an intellectual disability.